ESTIMASI PANJANG GARIS PANTAI PULAU SUMBAWA MENGGUNAKAN DIMENSI FRAKTAL - Muhammad Adriansyah; Rio Satriyantara; Afifurrahman; Marwan (MATHunesa: Jurnal Ilmiah Matematika, 2026)
This study aims to estimate the length of the Sumbawa Island coastline using a fractal geometry approach with the Box-Counting method. This method was chosen because it is able to describe the complexity and self-similarity of natural forms such as coastlines. Coastline image data was obtained from USGS Earth Explorer and processed using ArcGIS software and Python to perform edge detection. Calculations were performed at several map scales, namely 1:800,000, 1:900,000, and 1:950,000. The results show that the fractal dimension value of the Sumbawa Island coastline is relatively stable between 1.20882 and 1.21245, with an estimated coastline length ranging from 1702.79 km to 1760.86 km. The smallest error value of 0.1% was obtained at a scale of 1:800,000, which is considered to produce the most accurate estimate. These results indicate that the fractal approach is effective for estimating the length of complex coastlines, and provides a deeper understanding of the coastline paradox phenomenon in coastal geomorphology.